The utility of motor unit number estimation methods versus quantitative motor unit potential analysis in diagnosis of ALS. Issue 3 (March 2018) - Jacobsen, A.B.; Kristensen, R.S.; Witt, A.; Kristensen, A.G.; Duez, L.; Beniczky, S.; Fuglsang-Frederiksen, A.; Tankisi, H.
Highlights: Motor unit number estimate (MUNE) is more sensitive than motor unit potential (MUP) analysis in showing abnormality in abductor pollicis brevis muscle. Clinical measures do not correlate with MUNE parameters apart from a weak correlation with MScan. MUNE methods can increase the categorical probability of ALS. Abstract: Objective: To compare the diagnostic utility of motor unit number estimation (MUNE) methods to motor unit potential (MUP) analysis in amyotrophic lateral sclerosis (ALS). Methods: Twenty-five patients (1 definite, 11 probable, 9 possible ALS and 4 progressive muscular atrophy) and 22 healthy controls were prospectively included. Quantitative MUP analysis and three MUNE methods; Multiple Point Stimulation MUNE (MPS), Motor Unit Number Index (MUNIX) and MScanFit MUNE (MScan) were done in abductor pollicis brevis muscle. The sensitivities were compared by McNemar chi-square test. MUNE, MUP and revised ALS Functional Rating Scale (ALSFRS-R) parameters were correlated by regression analysis. Results: The sensitivities of MPS (76%) and MScan (68%) were higher than MUP duration (36%) and amplitude (40%) in detecting motor unit loss (p < 0.05). MUNE methods increased the categorical probability from possible to probable ALS in 4 patients (16%). There was only significant correlation between ALSFRS-R and MScan (r = 0.443, p = 0.027) among the electrophysiological tests. MUNE methods did not correlate to MUP parameters. Conclusions: MUNE methods are more sensitive in showing abnormality than MUP analysis. Significance: MUNE methods, in particular MScan, may have the potential to be implemented in the clinical practice for diagnosis and follow-up of neuromuscular disorders particularly ALS.